Teachers' and students' perceptions of formative feedback on L2 writing (2016)
This sequential explanatory mixed-methods research explored Colombian EFL teachers and students ' perceptions of feedback on writing in a foreign language. It gave a comprehensive account of the issue studied based on the data collected from different sources, such as surveys, focus groups, archival documents, artifacts and observations. Additionally, it served as a basis for further research on writing and assessment in foreign language leaming, giving recommendations to teachers and admimstrators regarding the use of formative feedback.